THU0102 High rates of residual disease activity despite current therapies in a real life rheumatoid arthritiscohort: data from 1096 patients. (12th June 2018) - Thomas, K.; Lazarini, A.; Kaltsonoudis, E.; Drosos, A.; Tsatsani, P.; Gazi, S.; Pantazi, L.; Boki, K.A.; Katsimbri, P.; Boumpas, D.; Fragkiadaki, K.; Tektonidou, M.; et al.
Abstract : Background: It is unclear if the widespread use of biologic DMARDs (bDMARDs) and the implementation of the treat to target approach have led to better disease control in patients with rheumatoid arthritis (RA) in daily clinical practice. Objectives: To study the longitudinal changes in disease activity in a large, real life, longitudinal RA cohort. Methods: Multicenter (11 hospitals, 3 private offices), prospective, RA epidemiological study in Greece. Demographics, disease characteristics, treatments and co-morbidities were collected via a web-based platform in registered patients at baseline and one year after their 1st visit. Results: 1.096 RA patients with available paired evaluations one year apart (mean interval: 13.4±3.6 months) were included (women: 78%, mean age: 62.8 years, mean disease duration: 11 years, RF and/or anti-CCP positive: 60%, mean HAQ: 0.44±0.56). At baseline, 50% (n=548) of patients were on conventional DMARDs (csDMARDs) alone, 35% on cs- and b-DMARD combination (n=379) and 11% on bDMARD monotherapy (n=124). Among bDMARD treated patients, 60% were receiving tumour necrosis factor inhibitors (TNFi) while 40% were on corticosteroids (mean daily dose: 4.7 mg). Despite these therapies, 43% of patients had active disease (DAS28-ERS>3.2); 34% moderate (MDA, DAS28-ESR=3.2–5.1) and 9% high (HDA, DAS28-ESR>5.1) disease activity. During the 1 year observation period, among the group of patients with MDA who were only on csDMARDs, 15% started a bDMARD while among those on bDMARDs, 11% switched to another bDMARD. The respective rates of starting a bDMARD (in those on csDMARDs) or switching to another bDMARD (in those on bDMARDs), were much higher for patients in the HDA group (41% and 32% respectively, p<0.001 for both groups). At the end of the 1st year, the proportion of patients on TNFi and corticosteroids was 57% and 32%, respectively. Overall, despite a decrease in the DAS28-ESR score (from 3.2±1.2 to 2.9±1.3, p<0.001), 37% of patients had still active disease (6% improvement after 1 year; MDA: 30%, HDA: 7%). Conclusions: In a large, real life, RA cohort with almost half of patients on bDMARD-based therapies, more than one third of patients had still active disease at the end of the 1st year of follow-up. These findings could be explained in part by the low rate of bDMARD initiation or switching in this cohort or they could indicate the limitations of current therapeutic approaches in RA patients with longstanding disease in Greece. Acknowledgements: Supported by grants from the Greek Rheumatology Society and Professional Association of Rheumatologists. Disclosure of Interest: None declared